Expression of the vesicular GABA transporter within neuromedin S+ neurons sustains behavioral circadian rhythms - Bussi, Ivana Leda (2023)
The suprachiasmatic nucleus (SCN) of the hypothalamus is the site of a central circadian clock that orchestrates overt rhythms of physiology and behavior. Circadian timekeeping requires intercellular communication among SCN neurons, and multiple signaling pathways contribute to SCN network coupling. Gamma-aminobutyric acid (GABA) is produced by virtually all SCN neurons, and previous work demonstrates that this transmitter regulates coupling in the adult SCN but is not essential for the nucleus to sustain overt circadian rhythms. Here, we show that the deletion of the gene that codes for the GABA vesicular transporter Vgat from neuromedin-S (NMS)+ neurons-a subset of neurons critical for SCN function-causes arrhythmia of locomotor activity and sleep. Further, NMS-Vgat deletion impairs intrinsic clock gene rhythms in SCN explants cultured ex vivo. Although vasoactive intestinal polypeptide (VIP) is critical for SCN function, Vgat deletion from VIP-expressing neurons did not lead to circadian arrhythmia in locomotor activity rhythms. Likewise, adult SCN-specific deletion of Vgat led to mild impairment of behavioral rhythms. Our results suggest that while the removal of GABA release from the adult SCN does not affect the pacemaker's ability to sustain overt circadian rhythms, its removal from a critical subset of neurons within the SCN throughout development removes the nucleus ability to sustain circadian rhythms. Our findings support a model in which SCN GABA release is critical for the developmental establishment of intercellular network properties that define the SCN as a central pacemaker.